Impact of Iron, Magnesium and Manganese on Arugula Chlorosis in Hydroponic Systems - Bazán Ramírez, Miguel Ángel (2023)
Iron (Fe) deficiency, in comparison with magnesium (Mg) and manganese (Mn) deficiencies, is an important factor that causes leaf chlorosis when growing arugula hydroponically. In this study, an experimental design was applied, using randomized complete blocks with four groups of six plants each: three experimental groups (EG) and one control group (CG). Precautions were taken to ensure that intervening variables such as artificial oxygenation and time did not affect the outcome of the experiment. The results obtained show that Fe, Mg, and Mn deficiency in each treatment influences the appearance of leaf chlorosis. Likewise, it is evident that the shortage of oxygenation and the excess of macronutrients influence the chlorosis and necrosis of the arugulae, respectively.